การเสริมสร้างความเข้มแข็งตามแนวคิดหุ้นส่วนทางสังคมในการจัดสวัสดิการสังคมขององค์กรสาธารณประโยชน์ - Kaewchur, Wichuta (Journal of Community Development Research (Humanities and Social Sciences), 2020)
แนวคิดหุ้นส่วนทางสังคมเป็นแนวคิดที่สำคัญในการส่งเสริมการมีส่วนร่วมของทุกภาคส่วนในการจัดสวัสดิการสังคมร่วมกันอย่างมีประสิทธิภาพ การศึกษาครั้งนี้ มีวัตถุประสงค์เพื่อศึกษาและวิเคราะห์แนวคิดหุ้นส่วนทางสังคมในการจัดสวัสดิการสังคมขององค์กรสาธารณประโยชน์โดยใช้ทฤษฎีวิพากษ์ และแนวทางการเสริมสร้างความเข้มแข็งตามแนวคิดหุ้นส่วนทางสังคมในการจัดสวัสดิการสังคมขององค์กรสาธารณประโยชน์ ซึ่งเป็นการศึกษาวิจัยเชิงคุณภาพ ด้วยวิธีการสัมภาษณ์เชิงลึกกับผู้บริหารหรือกรรมการขององค์กรสาธารณประโยชน์ประเภทองค์กรแม่ข่าย ผู้บริหารของหน่วยงานภาครัฐที่มีการทำงานด้านการจัดสวัสดิการสังคม และนักวิชาการ/ผู้เชี่ยวชาญ ซึ่งผลการวิจัยได้ ดังนี้           ผลการศึกษาการวิเคราะห์แนวคิดหุ้นส่วนทางสังคมในการจัดสวัสดิการสังคมขององค์กรสาธารณประโยชน์ โดยใช้ทฤษฎีวิพากษ์ สามารถวิเคราะห์ให้เห็นถึงบทบาทของแนวคิดหุ้นส่วนทางสังคมในการจัดสวัสดิการสังคมขององค์กรสาธารณประโยชน์ได้ในหลากหลายประเด็น แนวทางการเสริมสร้างความเข้มแข็งตามแนวคิดหุ้นส่วนทางสังคมในการจัดสวัสดิการสังคมขององค์กรสาธารณประโยชน์ เป็นการสร้างความร่วมมือ การต่างตอบแทน การควบคุม และการตรวจสอบระหว่างหน่วยงานภาครัฐและองค์กรสาธารณประโยชน์ ซึ่งการสร้างความร่วมมือซึ่งกันและกันมีแนวทางหลายประการ ส่วนการต่างตอบแทนซึ่งกันและกันจะเน้นการแบ่งปันความคิด ค่าใช้จ่าย และผลประโยชน์ร่วมกัน นอกจากนั้นการควบคุมซึ่งกันและกันมีการให้ความสำคัญกับการมีกฎหมายหรือกฎระเบียบ สำหรับการตรวจสอบซึ่งกันและกันจะเน้นการมีธรรมาภิบาลในการทำงาน           ข้อเสนอแนะในการศึกษาครั้งนี้ คือ หน่วยงานภาครัฐควรมีการส่งเสริมการนำแนวคิดหุ้นส่วนทางสังคมไปใช้ในการจัดสวัสดิการสังคมเพิ่มขึ้น การกำหนดนโยบายในการส่งเสริมให้ทุกภาคส่วนเข้ามามีส่วนร่วมเป็นหุ้นส่วนทางสังคมในการจัดสวัสดิการสังคมร่วมกันอย่างชัดเจน คำสำคัญ: แนวคิดหุ้นส่วนทางสังคม  การจัดสวัสดิการสังคม  องค์กรสาธารณประโยชน์           Social partnership concept is an important concept to promote all sectors to participate efficiently in social welfare provision. This research aimed to study and analyze the social partnership concept in the social welfare provision of public benefit organizations by using critical theory, providing guidelines to strengthening social welfare in public benefit organizations according to the social partnership concept. Qualitative research was done, with data gathered by in-depth interviews. Samples were managers and committee members of public benefit organizations including host organizations, managers of social welfare-associated government agencies, and academic experts.           Results were that analysis of the social partnership concept in the social welfare provision of public benefit organizations by using critical theory presented the role of the social partnership concept in the social welfare provision of public benefit organizations according to different issues. Guidelines for strengthening the social partnership concept in social welfare provision of public benefit organizations included creating cooperation, reciprocity, control, and inspection between government agencies and public benefit organizations. There were different ways to create cooperation. Reciprocity emphasized sharing of ideas, expenses, and mutual benefits. Moreover, the mutual control had focused on having the laws or the regulations. For the mutual inspection, it focused on good governance at work.           The recommendations of this study were that government agencies should promote the social partnership concepts to apply in social welfare provision, and the formulation of policies to encourage all sectors to participate in social partnership in providing social welfare clearly. Keywords: Social Partnership Concepts, Social Welfare Provision, Public Benefit Organizations